PRODUKSI NATA FRUTICANS DARI NIRA NIPAH - Mody Lempang (Jurnal Penelitian Hasil Hutan, 2013)
Nipah (Nypa fruticans Wurmb.) produces sap that can be obtained by tapping process from fruit stem. In fresh condition of nipah sap taste sweet cause of including relatively high of sugar. This liquid is a fertile medium for the growth of microorganisms, so that nipah sap is potentially used as a raw material to produce nata. Nata is a food that classified in food dissert. Experimental of nata fruticans production bold by fermenting process used fresh nipab sap that with sugar in level of 0, 50, 75 and 100 g/l of nipah sup. By using fresh nipah sap that add with sugar in vary level yielded nata fruticans with producing recovery an average of 86.05% (76,52-90,97%). The addition of sugar in the fresh nipah sap is not affect significantly on the producing recovery of nata fruticans. Using fresh nipah sap without sugar addition yielded nata fruticans with producing recovery an average of 83,74%.